2007
DOI: 10.1038/ng1955
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants account for differences in gene expression among ethnic groups

Abstract: Variation in DNA sequence contributes to individual differences in quantitative traits, but in humans the specific sequence variants are known for very few traits. We characterized variation in gene expression in cells from individuals belonging to three major population groups. This quantitative phenotype differs significantly between European-derived and Asian-derived populations for 1,097 of 4,197 genes tested. For the phenotypes with the strongest evidence of cis determinants, most of the variation is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
403
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(439 citation statements)
references
References 18 publications
(18 reference statements)
28
403
1
5
Order By: Relevance
“…However, no relationship was found between IL-17A gene polymorphisms at A-832G and silicosis now. The frequencies of genetic polymorphisms often vary between ethnic groups (Spielman et al, 2007), In the present study, the G allele frequency of A-832G was 0.293 among 116 control subjects, which is accord with the Chinese Han population (0.244) in SNP DataBase, but significantly lower than that of Sub-SaharanAfrican (0.372) population and European (0.783) population. (http://ww w.ncbi.nlm.nih.gov/SNP).…”
Section: Discussionsupporting
confidence: 79%
“…However, no relationship was found between IL-17A gene polymorphisms at A-832G and silicosis now. The frequencies of genetic polymorphisms often vary between ethnic groups (Spielman et al, 2007), In the present study, the G allele frequency of A-832G was 0.293 among 116 control subjects, which is accord with the Chinese Han population (0.244) in SNP DataBase, but significantly lower than that of Sub-SaharanAfrican (0.372) population and European (0.783) population. (http://ww w.ncbi.nlm.nih.gov/SNP).…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies (Knight 2004;Spielman et al 2007) have revealed that polymorphic variants can also be responsible for individual diVerences in expression level, and speciWc genetic variation among populations contributes appreciably to diVerences in gene expression phenotypes. These variations of gene expression and speciWc gene expression phenotypes could account for a large proportion of susceptibility to complex genetic disorders (Spielman et al 2007). Given this observation, the CA repeat may also play a role in the etiology of clefting.…”
Section: Discussionmentioning
confidence: 99%
“…Since phenotypic differences in gene expression between populations can be attributed to differences in frequencies of genetic variants, 61 it is possible that rs182309299 contributes to variation in CR2/CD21 expression levels between populations. Genotyping performed through the 1000 Genomes Project Phase 1 demonstrated the minor allele of this SNP is detected only in 1%-2% of individuals of African or African-American ancestry (Ensembl release 76, August 2014).…”
Section: Discussionmentioning
confidence: 99%